The solution of expression is,
⇒ x = 5.67
We have to given that;
Expression is,
⇒ 3x - 4 = 13
Now, We can simplify as;
⇒ 3x - 4 = 13
Add 4 both side, we get;
⇒ 3x - 4 + 4 = 13 + 4
⇒ 3x = 17
Divide by 3;
⇒ x = 17/3
⇒ x = 5.67
Thus, The solution of expression is,
⇒ x = 5.67
Learn more about the mathematical expression visit:
#SPJ6
Answer:
ok then
Step-by-step explanation:
sorryissseaaghenhiaate
(x+4)(x−9)=0 completing the square
square root property
4x² = 20
zero product property
Answer:
i) Zero product property
ii) Square root property
Step-by-step explanation:
(x + 4)(x -9) = 0
Here we are equating each factor equal to zero and find the solutions.
Therefore it is Zero product property.
4x^2 = 20
To find the value of x, we take the square root on both sides.
So it is square root property.
Hope this will helpful.
Thank you.
Answer:
The person above be is correct
Step-by-step explanation: